Islamic eco-cosmology in Ikhwan al-Safa’s view - Muhammad Abdullah Darras (Indonesian Journal of Islam and Muslim Societies, 2012)
This research aims to describe the root cause of ecological crisis happening atthe moment in terms of the cosmological-metaphysical views, by doing researchon the thoughts of a classical Muslim philosophical scientist group in 10th centuryAD called Ikhwan al-Safa’. To the author, Ikhwan al-Safa’ has a clear idea inviewing the universe holistically and intact as it is. Actually, this non-reductiveview was the typical main feature of medieval Islamic classical thought. However,the main reason of choosing the works of Ikhwan al-Safa’, especially their magnumopus Rasa’il Ikhwan al-S{afa’ , in the research is that Ikhwan al-Safa’ has puta lot of attention on the “wisdom of universe” in the ontological and epistemologicalstructure of knowledge that were developed in their work. With the mainconcepts such Love of Universe and Soul of Universe, Ikhwan al-Safa’ have givena holistic vision about the wisdom of the universe and the wisdom of the environmentitself.Pengkajian dalam artikel ini bertujuan untuk menguraikan akar masalah terjadinyakrisis ekologi yang terjadi saat ini dengan berangkat dari titik pijak berdasarkanperspektif kosmologis-metafisik. Yakni dengan melakukan penelitian terhadappemikiran kosmologi kelompok keilmuan-filosofis muslim klasik abad ke-10 Myang bernama Ikhwan al-Safa’. Bagi penulis, Ikhwan al-Safa’ memiliki pemikiranyang jernih dalam melihat alam semesta. Yakni melihat alam secara holistik dan utuh sebagaimana adanya. Sebenarnya pandangan khas yang non-reduktif inimenjadi ciri utama pemikiran klasik Islam abad pertengahan. Namun pemilihanpenelitian terhadap pemikiran Ikhwan al-Safa’ –terutama dalam karya magnumopusnyaRasa’il Ikhwan al-S{afa’ ini, lebih disebabkan karena kelompok ini bagipenulis, telah menaruh perhatian yang sangat kuat terhadap “kearifan alam”dalam struktur ontologis dan epistemologis keilmuan yang dikembangkan dalamkarya mereka. Dengan menguraikan beberapa konsep utama dalam kosmologiIkhwan al-Safa’, seperti alam sebagai sebuah kesatuan, jiwa semesta, dan cintasemesta, kita akan melihat bagaimana Ikhwan al-Safa’ memberikan sebuah visiholistik mengenai kearifan alam semesta dan kearifan lingkungan itu sendiri.